Impacts of heifer postweaning residual feed intake classification on reproductive and performance measurements of first-, second-, and third-parity Angus beef females. Issue 2 (5th April 2021) - Parsons, Cory T; Dafoe, Julia M; Wyffels, Samuel A; Van Emon, Megan; DelCurto, Timothy; Boss, Darrin L
Abstract: This study evaluated heifer postweaning residual feed intake (RFI ) classification on reproductive and performance measurements of first-, second-, and third-parity Angus beef females. We analyzed the annual, as well as, cumulative production of 347 Angus females from birth through weaning of their third calf. Heifer postweaning RFI was calculated as the actual dry matter intake minus the predicted dry matter intake based on the average daily gain of the contemporary group on an annual basis. Heifers were categorized based on RFI as either low (< −0.50 SD from mean), average (± 0.50 SD from mean), or high (> +0.50 SD from the mean) within year. There was no RFI × Parity interaction ( P ≥ 0.14) observed for all production/reproduction traits except for conception rates ( P = 0.02). Julian birth date of cows was influenced by RFI classification ( P < 0.01) and displayed a quadratic ( P = 0.02) effect with high RFI cows being born earlier in the calving season than average RFI cows (71.2 vs. 75.3 d), but did not differ from low RFI cows (74.0 vs. 75.3 d). Cow birth weight, weaning weight, as well as all other cow weight and body condition measurements were not influenced by RFI classification ( P ≥ 0.14). As expected, there was a linear increase in cow body weight at weaning with increasing parity ( P < 0.01). Cow RFI classification had no influence on progeny weaning weight, birth date, calving interval, or postpartum interval ( P ≥ 0.15). Calf birth weights displayed a quadratic parity effect ( P < 0.01) with first calf heifers having calves with lower birth weights than second- and third-parity calves. Calf 205-d adjusted weaning weights displayed a quadratic effect ( P = 0.01) with first calf heifers weaning lighter calves than second- and third-parity cows. Weaning weight ratio displayed a linear decrease with increasing parity ( P < 0.01). Cow conception probability displayed a linear tendency for pregnancy 2 ( P = 0.09), and a quadratic tendency for pregnancy 4 ( P = 0.07) as a function of RFI classification, but no effects were observed for pregnancy 1 and 3. Cow artificial insemination conception rates differed by year of pregnancy ( P < 0.01), but not RFI classification ( P = 0.81). In summary, heifer postweaning RFI classification had minimal effects on beef cattle production and reproductive efficiency.